Induction and Analysis of Anti-CD40-induced Colitis in Mice - Joyce-Shaikh, Barbara (Bio Protoc, 2019)
Colon inflammation or colitis affects more than 1 million people worldwide. Several pre-clinical models, including chemical-induced (i.e., DSS, TNBS) or pathogen-induced (i.e., Citrobacter rodentium) have been used to study mechanisms involved in the development and regulation of colitis. Anti-CD40 induced colitis model has gained acceptance to study the roles of innate immune cells during acute intestinal inflammation. Here we describe a rapid, robust and reproducible protocol to induce and analyze anti-CD40 mediated colitis in mice.